Bovine tuberculosis in brushtail possums (Trichosurus vulpecula) : studies on vaccination, experimental infection, and disease transmission : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University - Corner, L A L (Massey University, 2001)
The objectives of the research program were to obtain a better understanding of BCG as a tuberculosis vaccine in possums, and assess its potential as a tool for controlling tuberculosis in wild possum populations. A series of vaccination and challenge experiments were conducted, as well as studies on alternative experimental infection procedures. The program included two field studies, one on the epidemiology of tuberculosis in a population of possums regenerating after localised possum eradication, and the other examined the efficacy of BCG vaccine in a wild population in which tuberculosis was endemic. The first experiments confirmed the earlier published findings that BCG delivered as an intranasal aerosol induced a protective response. The protective response was found to be present 12 months after vaccination and therefore of sufficient longevity to make vaccination a practical control tool. A second study demonstrated that revaccination of possums enhanced protection and a third showed that conjunctival vaccination was as effective as intranasal aerosol. These findings supported the development of a possum activated self-vaccinator that would deliver vaccine as an aerosol. In delivering the spray to both the external nares and the eyes a simple and cheap device could be designed to efficiently vaccinate wild possums. The intratracheal experimental infection procedure used in the vaccination and challenge experiments was not entirely suitable for our purposes. Although it provided an assured level of exposure and repeatable results, all infected possums developed fulminant, rapidly progressive disease, irrespective of the vaccination regime used. Two alternative methods of challenge were examined; the conjunctival route of infection, and natural transmission between experimentally infected possums and susceptible in-contact possums. Conjunctival infection was shown to be a reliable procedure for infecting possums, with the disease that resulted from infection having many of the cardinal features of natural tuberculosis in wild possums. Infection following conjunctival inoculation progressed slowly and may be suitable for studying pseudo-vertical transmission and the efficacy of post-infection vaccination. In studies with captive possums there was little or no transmission of infection between experimentally infected possums and susceptible in-contact possums in the same pen when the experimentally infected animals were selected at random. However, when possums with high levels of social interaction were experimentally infected there was a significant increase in transmission rates. In addition, the possums that became infected by transmission were more socially active than those that remained free of infection. Two aspects of the pathogenesis of tuberculosis in possums were clarified during the experimental infection and natural transmission studies. The duration of preclinical infection, impossible to determine accurately in longitudinal studies on wild possums, was found to range from 6 - 20 weeks. Secondly, the pre-eminence of the aerosol route in naturally transmitted tuberculosis was confirmed. After eradication of possums from a 36 ha site, tuberculosis reappeared within four months. Re-emergence of infection on the site was due to immigration of infected possums, not to the survival of M. bovis in the environment. Each of the four restriction endonuclease analysis (REA) types of M. bovis that caused disease in the possum population showed a different temporal and spatial pattern. BCG vaccine had high efficacy in a wild possum population. Over 2 years, 300 possums were recruited to a study of BCG vaccination. Approximately 50% of the possums were vaccinated, where each possum was vaccinated using both intranasal aerosol and conjunctival instillation. There were significantly more cases of tuberculosis in unvaccinated possums than in vaccinates, with a relative risk of tuberculosis in unvaccinated possums of 3.21. The vaccine efficacy was 69%. The most important question relating to BCG vaccine that remains to be addressed is the ability of vaccination to control tuberculosis in possum populations. This research has demonstrated that BCG vaccine provided protection against M.bovis infection in both captive and wild possums. Future research should be directed towards developing delivery systems for vaccinating wild possums and strategies for vaccine use in wild tuberculous possum populations.
Keywords: Trichosurus vulpecula; Bovine tuberculosis; Tuberculosis in animals; Diseases; Vaccination; Disease prevention; New Zealand